THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON PROFITABILITY IN CONSUMER GOODS INDUSTRY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019 - 2020 - Tri Nur Rohmah (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This research on profitability aims to examine the effect of good corporate governance on profitability. The population in this research are Consumer Goods Industry companies listed on the Indonesia Stock Exchange in 2019 - 2020. The sample in this research was selected through purposive sampling, so that a sample of 104 companies was obtained. The statistical test tool uses multiple regression analysis. Profitability in this research was measured using Return on Assets, while good corporate governance was measured using external ownerships. The results show that external ownerships has no significant positive effect on profitability.